2018
DOI: 10.21277/sw.v1i8.323
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being of elderly people: the social factors

Abstract: <p>The article discusses the social factors of psychological well-being of elderly people. Psychological well-being is a personal phenomenon. It forms in the process of human activity and in the system of people`s real relationships with surrounding objects. In old age psychological well-being is determined by different factors. The social factor is one of them. It has been found that higher levels of psychological well-being have those elderly people who do not feel themselves lonely, who have enough op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…The fact that the care giver's communicative behavior with the older adults have a significant positive impact on improving their perceived psychological wellbeing results in the current study, is consistent with the results found in previous studies of ( Zimmerman et al, 2005;Tolson & Brown-Wilson, 2012;Hafskjold et al, 2015). These findings could be an indication that the shaping of the psychological well-being is determined by several factors, including but not limited to, personal, cognitive, and communicative factors (Kovalenko & Spivak, 2018). This lent further support for the present study findings, in which the linear regression analysis proved that the care givers' communicative behavior is a strong predictor of the perceived psychological wellbeing among the elders inside the assisted living facilities.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The fact that the care giver's communicative behavior with the older adults have a significant positive impact on improving their perceived psychological wellbeing results in the current study, is consistent with the results found in previous studies of ( Zimmerman et al, 2005;Tolson & Brown-Wilson, 2012;Hafskjold et al, 2015). These findings could be an indication that the shaping of the psychological well-being is determined by several factors, including but not limited to, personal, cognitive, and communicative factors (Kovalenko & Spivak, 2018). This lent further support for the present study findings, in which the linear regression analysis proved that the care givers' communicative behavior is a strong predictor of the perceived psychological wellbeing among the elders inside the assisted living facilities.…”
Section: Discussionsupporting
confidence: 86%
“…The findings of this study recorded that, older people have a strong will and needs of communication with caregivers and other people, even though their needs for safety and security might not be fulfilled (Wang, 2012). A compelling body of researches had also suggested that psychological well-being is significant in promoting longevity of older adults and increased their social engagement (Park, 2009;Kovalenko & Spivak, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study indicated that the level of social feelings of the elderly at the Ikhawanus Shawa Nursing Home is somehow low because several social feelings are not in accordance with Kovalenko & Spivak's (2018) theory. Social feelings are supposed to include a sense of solidarity, a sense of brotherhood, a sense of sympathy, trust, altruism, and a sense of affection.…”
Section: Elderly Social Feelingsmentioning
confidence: 65%
“…Building on previous studies, PWB may be associated with socio-demographic characteristics, health behaviors, and health status (Jia et al, 2021; Kovalenko & Spivak, 2018; Zhou et al, 2019). Considering the objectives of this study and the availability of data, we included the following control variables: (1) socio-demographic variables, including the respondents’ gender (1 = female , 0 = male ), age, years of education, marital status (1 = married , 2 = divorced , 3 = widowed , 4 = unmarried ), average annual household income, and the number of surviving children; (2) health behavior variables, including smoking, drinking, and exercise; these activities were descriptions of the current situation, and they were all indicated using “1 = yes” or “0 = no”; (3) health status variables, including self-rated health and the number of chronic diseases.…”
Section: Methodsmentioning
confidence: 84%